Tools and Algorithms for the Construction and Analysis of Systems: 24th International Conference, TACAS 2018, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018, Proceedings, Part II - Beyer, Dirk; Huisman, Marieke (Theoretical Computer Science and General Issues, 2018)
computer architecture; computer software selection and evaluation; formal logic; formal methods; model checker; model checking; multi core processors; program compilers; programming languages; semantics; software engineering; specifications; state space; verification